Identifying Implicit Process Variables To Support Future Empirical Work - Carver, Jeff; Basili, Victor (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2003)
The most basic questions that researchers must address when introducing a new process or technique are what is the intended effect of that process and can that effect be demonstrated empirically. As the understanding of a process progresses, researchers become interested in more sophisticated questions about a process or technique, such as studying the relationship between a particular type of variable and the outcome of the process. Quite often, researchers will find few, if any, studies in the literature that explicitly identify and analyze the effects of potential variables on the process. This paper proposes a methodology to aid in performing a literature search to be used as a basis for new research into these types of variables. The methodology provides guidance on making use of a large range of studies from which to extract potential variables. Throughout the paper, the methodology is illustrated with a specific example. The example focuses on searching for variables that deal with individual variations among software inspectors that affect their performance during an inspection. At the end of the example, after following the steps of the methodology, a list of potential variables among software inspectors is identified. The paper concludes with the next steps to be taken concerning the identified variables and hypotheses.